Italian Studies - Cooper, Martin (2013)
The results of the analysis of data related to the implementation of the Italian assessment task over the three years are presented in this chapter starting with a discussion of the implementation of the task and the technologies employed. This is followed by descriptions and findings for each year from an analysis of the data resulting from assessing the student work and the qualitative data concerning implementation and the perceptions of participants.